Transformasi Pembelajaran PAI melalui Strategi Ekspositori dan Interactive Flat Panel Display (IFPD) - Windi Ariani; Wahyuni Ahadiyah (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2025)
This research, entitled “Implementation of the Expository Strategy Assisted by Interactive Flat Panel Display (IFPD) Media in Islamic Religious Education (PAI) Learning for Grade VIII Students at SMP Al-Musaa’adah Tikung,” is motivated by the need of PAI teachers to improve the effectiveness of learning by combining the expository strategy with the use of IFPD media. The traditional lecture method was previously considered less effective in stimulating student interest, whereas the use of IFPD is believed to enhance the delivery of material in a more engaging and interactive way, particularly in the lesson "Believing in the Prophets and Messengers of Allah: Becoming a Digital Generation with Character." The purpose of this study is to describe the implementation of the expository straThis research, entitled “Implementation of the Expository Strategy Assisted by Interactive Flat Panel Display (IFPD) Media in Islamic Religious Education (PAI) Learning for Grade VIII Students at SMP Al-Musaa’adah Tikung,” is motivated by the need of PAI teachers to improve the effectiveness of learning by combining the expository strategy with the use of IFPD media. The traditional lecture method was previously considered less effective in stimulating student interest, whereas the use of IFPD is believed to enhance the delivery of material in a more engaging and interactive way, particularly in the lesson "Believing in the Prophets and Messengers of Allah: Becoming a Digital Generation with Character." The purpose of this study is to describe the implementation of the expository strategy assisted by IFPD and to explore how the media is used in the PAI learning process for Grade VIII students at SMP Al-Musaa’adah Tikung. This study uses a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The research subjects consist of PAI teachers, Grade VIII students, and the school principal. Data were analyzed inductively through the processes of data reduction, data display, and conclusion drawing. The findings show that the expository strategy assisted by IFPD in Grade VIII at SMP Al-Musaa’adah Tikung was implemented in a structured manner through lectures supported by visual media and utilized as an interactive tool to enhance students’ understanding and engagement in Islamic Religious Education learning.tegy assisted by IFPD and to explore how the media is used in the PAI learning process for Grade VIII students at SMP Al-Musaa’adah Tikung. This study uses a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. The research subjects consist of PAI teachers, Grade VIII students, and the school principal. Data were analyzed inductively through the processes of data reduction, data display, and conclusion drawing. The findings show that the expository strategy assisted by IFPD in Grade VIII at SMP Al-Musaa’adah Tikung was implemented in a structured manner through lectures supported by visual media and utilized as an interactive tool to enhance students’ understanding and engagement in Islamic Religious Education learning.